Can Deliberative Policy Reconcile Religious Conflict? A Construction from the Insight of Jamaah Ahmadiyah Indonesia - Ihsan Rahmat; Indra Pratama Putra Salmon; Amrih Setyo Raharjo (NALAR, 2021)
The state has failed to manage religious conflicts. Not only from the side of the government apparatus, which helped provoke the mass to the loss of life, but also weak and biased central regulations. The fact is that national policies do not complete the agenda and content of interests. This study argues that an important deliberative policy is made in each conflict area as a reinforcement for national policy. We construct a deliberative policy flow for religious conflicts based on academic guidelines and the case of the Jamaah Ahmadiyah Indonesia (JAI) in Colo Village, Kudus Regency, Central Java Province. This study is sourced from data collected in November 2018 through documentation, interviews, and observations. We have interviewed the village government, religious leaders, active congregations, and residents. The results of the interviews were processed through the process of transcription, determining keywords, categorizing, and defining. Data refined in October 2020 through literature studies and news clipping. We have described policies as triggers of conflict, identified four patterns of JAI conflict in Indonesia, and explained the dynamics of Ahmadiyyah diversity with local Muslims in Colo. Primarily, this study contains a deliberative policy-making process. The key to this policy is a participatory, informative, balanced, and thorough discussion of all parties. The task in the future is the need to examine the deliberative policy flow that we have constructed to ensure that this can be applied.Keywords : Religious Conflict; Deliberative Policy; Jamaah Ahmadiyyah Indonesia